Análisis financiero y la toma de decisiones de la Cooperativa de Ahorro y Crédito Innovación Andina LTDA., del cantón Latacunga, periodo 2021-2022. - Basurto Arauz, José Fabricio (2023)
Face to economy demands globalized, there is a need to carry out financial analysis that contributes to decision-making through financial strategies an operating model in COAC Innovación Andina del Cantón Latacunga, period 2021-2022. The applied methodology under a quantitative approach, which uses numerical data, through a documentary bibliographic research modality through reviews in reliable sources, with a type of descriptive and correlational research, since it describes the causes and effects of economic events. As results, it determined that COAC had a growth in 2022 due to increase in assets by 30.80%, equity by 45.65%, and liabilities by 22.22%, however, liabilities with costs were managed and placed efficiently, delinquency was controlled, which decreased by -2.05%, due to the strategies implementation through a program of economic incentives to personnel in charge of placing loans, profitability (ROE) grew by a 0.02% as a result of a better return on invested capital by the partners, with respect to the (ROA) it was favorable, which allowed strengthening the capital referring to the invested asset, liquidity for the last year increased by a percentage of 22.78%, due to the increase in available funds and the recovery of the overdue portfolio. It is determined that there is an adequate management and a frank growth of the COAC in 2022, however, it must manage the operational expenses themselves, which had an personnel increase of 12.60%, by 41.12%, according to horizontal analysis, in addition, unproductive and productive assets were not managed efficiently. Therefore, it is concluded with the need to propose financial strategies to COAC management through an operating model aimed at decision making.